Angels : the concept of celestial beings : origins, development and reception - Reiterer, Friedrich V. (Friedrich Vinzenz), 1947-; Nicklas, Tobias, 1967-; Schöpflin, Karin, 1956- (Deuterocanonical and cognate literature yearbook, 2007)
In our present-day society "Angels" are being talked about more frequently again. But where are the roots of these discourses to be found? How have they developed?The present volume focuses on important sources for the investigation of angelic images wi.